2018
DOI: 10.1038/s41408-018-0145-9
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide plus R-CHOP21 in newly diagnosed diffuse large B-cell lymphoma (DLBCL): long-term follow-up results from a combined analysis from two phase 2 trials

Abstract: Lenalidomide-RCHOP (R2-CHOP21) has been shown to be safe and effective in patients with untreated diffuse large B-cell lymphoma (DLBCL). The aim of this analysis is to report long-term outcome and toxicities in newly diagnosed DLBCL patients who received R2-CHOP21 in two independent phase 2 trials, conducted by Mayo Clinic (MC) and Fondazione Italiana Linfomi (FIL). All patients received R-CHOP21 plus lenalidomide. Long-term progression-free survival (PFS), time to progression (TTP), overall survival (OS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 32 publications
0
22
0
2
Order By: Relevance
“…Meanwhile, lenalidomide could exert direct tumor toxicities via binding to cereblon to inhibit downstream NF-κB signaling [ 33 ]. Combination of lenalidomide and R-CHOP21 (R2-CHOP) seemed to provide benefits in several phase 2 studies, especially for the non-GCB and high-risk subgroups [ 34 ]. In REMARC study, for elderly patients responding to first-line R-CHOP, lenalidomide maintenance for 24 months prolonged PFS over placebo, although no OS benefit was found [ 35 ].…”
Section: Immunotherapymentioning
confidence: 99%
“…Meanwhile, lenalidomide could exert direct tumor toxicities via binding to cereblon to inhibit downstream NF-κB signaling [ 33 ]. Combination of lenalidomide and R-CHOP21 (R2-CHOP) seemed to provide benefits in several phase 2 studies, especially for the non-GCB and high-risk subgroups [ 34 ]. In REMARC study, for elderly patients responding to first-line R-CHOP, lenalidomide maintenance for 24 months prolonged PFS over placebo, although no OS benefit was found [ 35 ].…”
Section: Immunotherapymentioning
confidence: 99%
“…9 In combination with R-CHOP (R2-CHOP), lenalidomide has acceptable levels of toxicity and may mitigate the negative prognosis of the non-GCB phenotype. 7,[10][11][12][13][14] It has also been suggested that the clinical benefit of lenalidomide monotherapy in patients with DLBCL was more evident in the gene-expression profiling (GEP)-defined ABC population. 15 On the basis of these data, we designed a randomized phase III clinical trial to determine the tolerance and efficacy of the R2-miniCHOP regimen in comparison to R-miniCHOP in patients older than 80 years with newly diagnosed DLBCL.…”
Section: Introductionmentioning
confidence: 99%
“…А. Castellino и соавт. [15] опубликовали отдаленные результаты, доказывающие преимущества программы R2-CHOP, где в группе больных non-GCB-ДВККЛ 5-летняя БПВ и ОВ составили 64,5 и 74,1 %. В анализируемой группе у 88 % была диагностирована III-IV стадии заболевания, у 56 % IPI составил 4-5 баллов.…”
Section: Discussionunclassified
“…В ряде работ показана высокая эффективность применения монотерапии леналидомидом у больных с рецидивом и прогрессией АВС-ДВККЛ [9,10], а также в качестве первой линии в сочетании с ХТ по схеме R-CHOP [11][12][13][14][15].…”
unclassified